PERENCANAAN PARIWISATA DI PULAU KERA KABUPATEN KUPANG PROVINSI NUSA TENGGARA TIMUR - Ida Ayu Lochana; Dedi Soedharma; Soehartini Sekartjakrarini (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Tourism is one of development sector that can develop in the small Island. Kera Island is a part of Kupang Bay Natural Sea Tour in Nusa Tenggara Province. Tourism planning in Kera Island is a part of suistenable development strategi which developed with ecotourism. The research had been conducted in Kera Island, Kupang Regency, NTT Province for six months (July, 2005 and February-July 2006). Aim of this researct was to know the carakteristic of Kera Island characteristic for tourism planning. The result of this research is Kera Island has potensial environment for tourism. The Coastal of Kera Island had two Plant comunities. There were pest-caprae (Ipomea pes-caprae) and Barringtonia (Barringtonia spp.), whice made six type of their assosiation. They are Ipomoea pes-caprae and Spinifex littoreus (4,56 ha), Ischaemum muticum (14,37 ha), Andropogon halepense (6,37 ha), Sterculia sp. (10,29 ha), Sesbania grandiflora (7,57 ha), and Sporobolus sp. (2,01). Some tour attraction in Kera Island are sun bathing, tracking, camping, eduacation tour, and relegius tour. According to carring capacity analized, the beach of Kera Island would visited 39-210 person for deluxe klas. Camping area and Bajo traditional house or Timor traditional house are the first acomodation alternatif in the Kera Island tourism planning. Both of camping area and traditional house would take place in Iscaemum muticum area, Sterculia sp. area, and Andropogon halepense area. The reson of its statement is small size of Kera Island (48 ha). The strategy for community development are sea weeds aquaculture programe and in formal tourism education programe. Key words: ecotourism, carring capacity, traditional house, comunnity development